The dynamics of neurogenic signalling underlying bristle development in Drosophila melanogaster. - Parks, A.L.; Huppert, S.S.; Muskavitch, M.A. (Mechanisms of Development, 1997)
We have examined expression of the neurogenic gene, Delta (Dl), and the regulatory relationships between the Delta-Notch signalling pathway and the proneural gene, achaete, during microchaeta development in Drosophila. Delta is expressed in all microchaeta proneural cells and microchaeta sensory organ precursors (SOPs) and is expressed dynamically in SOP progeny. We find that Delta expression in microchaeta proneural cells is detected prior to the onset of achaete expression and arises normally in the absence of achaete/scute function, indicating that initial Delta expression in the notum is not dependent on proneural gene function. Activation of the Delta-Notch pathway results in loss of Delta protein accumulation, suggesting that Delta expression is regulated, in part, by Delta-Notch signalling activity. We find that Delta signalling is required for correct delineation of early proneural gene expression in developing nota. Within microchaeta proneural stripes, we demonstrate that Delta-Notch signalling prohibits adoption of the SOP fate by repressing expression of proneural genes.